An adaptively focusing measurement design for compressed sensing based DOA estimation - Ibrahim, Mohamed; Roemer, Florian; Del Galdo, Giovanni (2015 23rd European Signal Processing Conference, EUSIPCO 2015, 2015)
In this paper we propose an adaptive design strategy for the measurement matrix for applying Compressed Sensing (CS) to Direction Of Arrival (DOA) estimation with antenna arrays. Instead of choosing the coefficients of the compression matrix randomly, we propose a systematic design methodology for constructing a measurement matrix that focuses the array towards a specific area of interest and thereby achieves a superior DOA estimation performance. The focusing is performed in a sequential manner, i.e., we start with a uniform measurement design from which regions of interest can be extracted that the subsequent measurements then focus on. By continuously updating these target regions, gradual movement of the sources can also be tracked over time. Numerical results demonstrate that the focused measurements possess a superior SNR leading to significantly enhanced DOA estimates.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Compressive Sensing; DOA Estimation; Measurement Design